The Effect of Different Feeding on Growth in Morkaraman Male Lambs - Şahinler, Z; Demir, Y; Gürsoy, E (Journal of the Hellenic Veterinary Medical Society, 2023)
The object of this study is to compare the concentrated feeding under intensive conditions with the traditional two feed types applied in the Morkaraman lambs feeding in Ağrı province. By forming 3 groups having 15 heads in each with random sampling after the male lambs weaned (75th day), each group was fed with different feeding. The 1st group was subjected to traditional day and night lactation beside grazing on pasture, 2nd group was subjected to ad-libitum concentrated feed and hay- clover under intensive conditions, the 3rd group was subjected to traditional pasture grazing. For the Morkaraman male lambs; 75th day (per feeding) and 135th day (end of feeding) average live weights are found for 1st, 2nd and 3rd groups and in general order as 21.27±0.819, 20.65±0.564, 20.57±0.824, 20.83±0.423kg and 33.43±0.727, 35.88±0.875, 26.95±1.084, 32.08±0.765 kg respectively. Regarding the 75th day live weights, the differences among three groups are similar and insignificant, regarding the 135th day live weights are similar in the 1st and 2nd groups, and the differences (p<0.01) with the 3rd group are important. Daily live weight gains on 75-90th days live weight gains are similar in the 1st and 2nd groups, the difference with the 3rd group is significant (p<0.01), regarding the 105-120th and 120-135th days the differences among three groups are found statistically significant (p<0.01). This study revealed not only the insufficiency of the lamb feeding on the low-quality pastures but also the inadequacy of the growth of the lambs sucking dams fed on the low-quality pastures and the lambs grazing on these pastures as well. As a result, it is concluded that the concentrated feed under intensive conditions is more efficient on lamb growth; however, the feeding of the lamb and dam grazing on pasture should be supported by a supplementary feeding. Keywords: Morkaraman; live weight gain; lamb growth; pasture